Exploring Violence Socialization and Approval of Intimate Partner Violence Among University Students in Kosovo - Kelmendi, Kaltrina; Baumgartner, František (Journal of interpersonal violence, 2020)
Intimate partner violence (IPV) among university students is a prevalent problem in many countries; however, it is not currently recognized in Kosovo as a social issue in terms of research, prevention, and intervention. The aim of this article was to examine the relationship between violence socialization experiences, approval of violence, and IPV perpetration/victimization among university students in Kosovo. The questionnaires were administrated to a convenience sample of 700 students of University of Prishtina who were in relationship for 1 month or longer. The Revised Conflict Tactics Scale (CTS-2) was used for measuring physical, psychological, and sexual violence, whereas for measuring violence socialization and violence approval, scales from Personal and Relationships Profile (PRP) were used. Findings from this study show that there were statistically significant gender differences in terms of socialization and approval of violence among university students. Similarly, perpetrators and victims of IPV (physical, psychological, and sexual violence) showed higher rates of socialization of violence and tolerance toward IPV. Besides, findings indicate that approval of violence mediates the relationship between socialization of violence and IPV perpetration and victimization, for both genders. The implications of the current findings within a cultural context are also discussed.
Keywords: Young Adult; Social Behavior; studenti; Male; mladý dospělý; Attitude; sexuální faktory; Intimate Partner Violence; Adult; dating violence; dospělí; násilí; mužské pohlaví; Violence; analýza mediace; násilí mezi partnery; Socialization; lidé; ženské pohlaví; intergenerational transmission of trauma; Students; domestic violence; Humans; postoj; Sex Factors; socializace; Mediation Analysis; sociální chování; Universities; univerzity; Female; violence exposure; Kosovo